Corrosion and tribocorrosion behaviour of titanium nitride thin films grown on titanium under different deposition times - Çaha, I. (2019)
Ti and its alloys exhibit combination of unique properties for biomedical applications, however their poor tribo-electrochemical behaviour is a major concern. Therefore, TiN coatings were deposited on cp-Ti (grade 4) by sputtering technique aiming the improvement of its tribocorrosion behaviour. The properties of the coated samples, using different TiN deposition times, were characterized by using grazing incidence X-ray diffraction, FIB-SEM, and nanoindentation. The corrosion behaviour was studied by electrochemical impedance spectroscopy and potentiodynamic polarization in 9 g/L NaCl solution at body temperature. Tribocorrosion tests were employed under open circuit potential by using a ball-on-plate tribometer with 1 N normal load, 3 mm total stroke length, 1 Hz frequency, and 1800 s sliding duration. The results suggested that the TiN coatings deposited during 80 min presented better corrosion and tribocorrosion behaviour as compared to the bare metal and TiN coatings deposited during 30 min.